Interest rate policy, inflation and economic growth A Policy Evaluation of Indonesia, 1969-1997 - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Pascasarjana UGM, 2004)
According to Shaw ( 1973) and McKinnon (1973), the most important element of economic development is financial liberalization. This action will eliminate the distortion, as what the government of Indonesia did on June 1, 1983 through deregulation of banking. The government eliminated the ceiling of credit and gave afull authority to each bank to determine their interest rates. This study looks up to Fry (1995) model to test McKinnon-Shaw hypothesis. The models were regressed with dummy variable. This effort will give illustration or conclusion of the structural change, that happened specifically caused by environmental or policy changes. Generally, insignificant in the relationship between interest rates in national saving and investment in Indonesia could be caused by financial mechanisms those very long and complex channels. That is why real interest rates: could not give effect to national saving directly. Export, especially from oil and gas and foreign debt were growth-stimulating factors. Meanwhile, money supply, which supported by tight money policy and balance budget policy caused Indonesian inflation along those periods. The periodically analysis shows that deregulation of June 1983(PAKJUN) were success to mobilize public fund, encourage investment on real sector, and increase the economic growth, but failed to control the inflation rate. The implementation of October 1988 deregulation (PAKTO) had flourished the establishment of new banks and created good competition among them. The competition had no longer on interest rate. Therefore, it can be said also the easy requirements of establishing banks become contra productive forPAKJUN policy, which had laid to the market mechanism. Basically, either PAKJUN or PAKTO was not policies in which urgently implemented in Indonesia. Those financial deregulations were not supported by the existence of deregulation on real sectors, so that the financial deregulations were not effective to achieve their goals.